2007
DOI: 10.1007/s11568-008-9016-y
|View full text |Cite
|
Sign up to set email alerts
|

The geography of genetics: an analysis of referral patterns to a cancer genetics service

Abstract: This study uses a geographical information system (GIS) and statistical analysis to look for patterns in referrals to a British cancer genetics service. In this case, familial cancers are taken to be those that can develop when an individual inherits DNA mutations that cause an increased risk of cancer. Between 1998 and 2006 the Cancer Genetics Service for Wales received nearly 11,000 referrals for patients resident in Wales and it is the service database recording those referrals which is the subject of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Five papers described service organisation, identifying inequity and variability in provision, and lack of co-ordination between genetics and non-genetics services. [6][7][8][9][10] Two reviews of specialised services in the UK found variation in referral and genetic testing rates between regions, 6 and an inverse relationship between referrals and deprivation. 7 Variability was also reported in a survey of the US Veterans Health Administration (VHA) genetics services.…”
Section: Service Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Five papers described service organisation, identifying inequity and variability in provision, and lack of co-ordination between genetics and non-genetics services. [6][7][8][9][10] Two reviews of specialised services in the UK found variation in referral and genetic testing rates between regions, 6 and an inverse relationship between referrals and deprivation. 7 Variability was also reported in a survey of the US Veterans Health Administration (VHA) genetics services.…”
Section: Service Organisationmentioning
confidence: 99%
“…[6][7][8][9][10] Two reviews of specialised services in the UK found variation in referral and genetic testing rates between regions, 6 and an inverse relationship between referrals and deprivation. 7 Variability was also reported in a survey of the US Veterans Health Administration (VHA) genetics services. 8 Services were largely delivered through multidisciplinary clinics or coordinated services, but this was not consistent.…”
Section: Service Organisationmentioning
confidence: 99%